Comunicação e Movimento na poética do compositor Chico César: os usos da Diáspora Africana na música negra no Brasil - Silveira, Dener Santos (Universidade Federal de São Carlos, 2018)
The present work analyzes the Brazilian black music from the songs and the cultural work of the singer and composer Francisco César Gonçalves - Chico César - born in the municipality of Catolé do Rocha in the sertão of the State of Paraíba / PB northeast region of Brazil. In the 1990s, the composer abandoned his career linked to journalism and entered the Brazilian music scene, after participating in music festivals in Germany. Featuring a creative poetics in his productions, Chico César begins his career as a musician and composer in the city of São Paulo / SP rescuing a sertanejo (sertão da paraíba) framework and an Africanized grammatical lexic. The set of lyrics of the composer is classified as "communication" and "movement" and is projected with diasporic production, since it disarticulate the logic of the idea of ​​nation present in the analyzes on "Brazilian popular music". The construction of music in Brazil, through Bossa-Nova and later Tropicália, which were understood as reactive movements to a kind of national-popular movement in music, is reoriented by the use of the African diaspora in the sense of African dispersion - creation and recreation of a sense of belonging determined by situations of oppression. The strategy to achieve this goal was to deconstruct the essentialization of difference by repositioning the tensions of the Afro-Atlantic style of the black repertoire and the body. The thesis is that the linguistic innovations (communication) and the transnational re-Africanized lexicon (movement) present in the lyrics, the forms of occupying a social space, hair styles, and the means to constitute and sustain community bonds are responses provided by music of the African Diaspora in reaction to Brazilian popular music. The idea is that the Africanized cultural production of Chico Cesar is critical and dismantles the theater of popular desires which is submitted by the notion of nationality, because from its social development, it constructs a new cultural politics of representation as a new ideological complex and theoretical.
Keywords: Diáspora Africana; Chico César; Música; Relações raciais; African Diaspora; Music; Race relations; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS